Insecticidal activity of crude olive pomace oils from Kabylia (Algeria) against the infestation of Rhyzopertha dominica (F.) and Sitophilus oryzae (L.) in stored wheat grains - Kerbel, Safia; Azzi, H; Kadi, H; Fellag, H; Debras, J-F; Kellouche, A (African Entomology, 2024)
The insecticidal effect of four crude olive pomace oils extracted from pomace collected from four localities of Kabylia, refined olive pomace oil and extra virgin olive oil were assessed under laboratory conditions for the control of adults of Rhyzopertha dominica (Fabricius, 1792) (Coleoptera: Bostrychidae)) and Sitophilus oryzae (Linnaeus, 1763) (Coleoptera: Curculionidae). The doses used ranged from 0.1 to 0.4 ml/25 g of durum and soft wheat seeds. In addition, the quality indices and the fatty acid composition of these oils were evaluated. The results show that the legal quality indices were well within the legal limits for crude olive-pomace oil (COP), refined pomace oil (ROP) and extra-virgin olive oil (EVO) categories. The effectiveness of these vegetable oils is highly dependent on the insect species, the dose rate, the exposure time and the type of oil tested The main fatty acids from all samples tested, were oleic (61.89–79.25%), palmitic (8.34–15.71%) and linoleic (8.17–16.52%) acids. For both species and substrates tested, mortality is dose and time of exposure dependent. The highest dose (0.4 ml/25 g) causes ≥ 63.75% mortality, after 24 h of exposure. Comparison of LD50 (ml/25 g) indicates that olive oil was generally more toxic than crude and refined pomace oils, for both insects and substrates, values varies from 0.005 to 0.189. The most sensitive insect was S. oryzae for most vegetable oils tested. Likewise, oils significantly reduced the F1 offspring of both insects and seed weight losses. No progeny were observed in the two pests at the highest dose, and therefore no weight loss was recorded. The results also revealed that the six oils affect the germination capacity of durum and soft wheat seeds when the dosage is increased. The results collected remain encouraging for the recommendation of natural substances as part of integrated pest management programmes against insect pests of stored grains.